Comparison of Fixed and Age-Sex-Adjusted NFPA Standards for Cardiopulmonary Fitness in Thai Wildland Firefighters - Jinjuta Panumasvivat; Pheerasak Assavanopakun; Kampanat Wangsan; Vithawat Surawattanasakul; Wachiranun Sirikul; Pannawich Chantaklang; Thitirat Vinsirivorakul (Journal of Occupational & Environmental Medicine, 2026)
Objective: This study examined Thai wildland firefighters' cardiopulmonary fitness, comparing previous and updated NFPA criteria. Methods: Chiang Mai wildland firefighters' health was cross-sectionally examined. Chester Step cardiopulmonary fitness was assessed using the fixed 12-MET threshold and age- and sex-adjusted 50th percentile criterion. McNemar test indicated standard concordance, and multivariable linear regression found MET values. Statistical significance was assigned by p-values < 0.05. Results: Significant differences in fitness classifications between two methods (p < 0.05). Two previously passed participants failed, while 13 previously failed participants passed. Age (B=-0.07; 95% CI: -0.13, -0.01; p=0.016) and resting heart rate (B=-0.11; 95% CI: -0.16, -0.07; p